Early diagnosis of Scots pine trees for resistance to annosum root rot - Дишко , В. А.; Усцький , І. М.; Торосова , Л. О. (Forestry and Forest Melioration, 2022)
Introduction In pine stands affected by annosum root rot (Heterobasidion annosum s.l.), there are Scots pine (Pinus sylvestris L.) trees that are able to maintain viability for a long time without showing external signs of the disease (“conditionally resistant”). Establishing forest stands with seeds from such trees can significantly increase the effectiveness of artificial reforestation. Scientists have noted that the growth and development of pine are to some extent determined by the cotyledons number in the germinants. Nowadays it is an urgent issue to develop methods for early diagnosis of hereditary properties in order to predict the characteristics of an adult plant. The study aimed to analyse the possibility of using signs of cell mitotic activity of root apical meristems and a number of cotyledons in Scots pine germinating seedlings to predict the tree resistance to annosum root rot. Materials and Methods The study site is located in the northeastern part of Ukraine in the State Enterprise “Kharkiv Forest Research Station” (Kharkiv region). In the stand affected by root fungus, trees with different health conditions were selected, namely without external signs of decline (“conditionally resistant” – 13 trees), with signs of disease (“affected”– 7 trees) and control (5 trees). Cones were collected from the selected trees and seeds were removed. Seed samples of 100 seeds from each tree were taken. The sowing qualities of seeds (germination) and their weight were evaluated according to the methods generally accepted in forest seed production. We evaluated the mitotic activity of root cells and counted a number of cotyledons in germinating seedlings. Then, we analysed in variants the distribution of frequency of seedlings with different numbers of cotyledons. Results The seeds of “conditionally resistant” trees exceed those of “affected” and control trees by mass by 18.5% and 5%, respectively. There is no significant difference in the energy of seed germination between the seeds of trees with different resistance (65% and 64%, respectively). The proliferative activity of apical meristem cells of “conditionally resistant” trees is significantly higher than that of “affected” ones (tCt = 8.5; t0.01 = 4.0) and control (tCt = 5.1; t0.01 = 4.0). The biggest differences between germinating seedlings from the seeds of “conditionally resistant" and “affected” trees were found in the percentage of prophases (36.7% and 42.0%, respectively) and metaphases (32.7 and 25.7%, respectively). The number of cotyledons in germinants varied from three to nine. Germinating seedlings with six cotyledons were most often found in the samples. The total share of seeds whose seedlings had more than six cotyledons made 84.6% in “conditionally resistant” trees, 75.9% in “affected” trees and 80.71% in the control. Conclusions The seeds of “conditionally resistant” trees compared to “affected” ones are characterized by a larger average weight of 1,000 seeds and are not inferior in terms of their germination energy. The stability of the level of mitotic activity of cells in the roots of germinating seedlings of “conditionally resistant” trees as well as its greater intensity compared to “affected” ones were confirmed (MI = 10.7% and MI = 5.6%, respectively, where MI is mitotic index). Most often, the samples contain germinants with six cotyledons. The maximum total share of germinating seedlings in which a number of cotyledons were 6 or more was recorded for “conditionally resistant” trees. Based on the findings, we preliminarily recommend the use of the set above features for the diagnosis of resistance to annosum root rot among the young trees that have entered reproduction. Further research is necessary to definitely confirm or refute our hypothesis. The use of indicators of the mitotic activity of apical meristem cells and a number of cotyledons of germinating seedlings for the early assessment of Scots pine trees for their resistance to annosum root rot can increase the effectiveness of selection by these features. The application of cytological methods can be especially relevant in progeny tests, which should be established for the study of the inherited resistance traits. 3 Fig., 2 Tables, 27 Refs.